Faktor-faktor yang mempengaruhi kinerja auditor internal perusahaan - Donito, Vanne; Trisnaningsih, Sri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze and explain what factors affect the performance of internal auditors from goods and service procurement companies PT. KAI DAOP 8.. This study uses quantitative methods with a population of 80 internal auditors from goods and service procurement companies PT. KAI DAOP 8. Sampling using simple random sampling technique and obtained a sample of 67 samples. The technique used in this study is multiple linear regression analysis using SPSS software. The results are auditor independence, organizational commitment, understanding of good governance, leadership style, and organizational culture have a significant and positive effect on the performance of the company's internal auditors.